2021
DOI: 10.3390/molecules26164975
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Methylene Blue and Its Metabolite Residues in Aquatic Products by High-Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: A sensitive and reliable method was developed to determine methylene blue (MB) and its metabolite residues, including azure A (AZA), azure B (AZB), and azure C (AZC) in aquatic products by HPLC–MS/MS. The samples were extracted by acetonitrile and cleaned up by alumina-neutral (ALN) cartridges. The analytes were separated on a Sunfire C18 column (150 mm × 2.1 mm, 5 µm). The method was validated according to the European criteria of Commission Decision 2002/657/CE. Good linearity between 1–500 µg/L was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…5 c show that in more than 225 μL, all the dye enters the eluent, and the equilibrium moves quantitatively toward the eluent and becomes completely desorbed. Zhang et al (2021) obtained similar results in the extraction of methylene blue (MB) dye using alumina-neutral (ALN) cartridges 44 . Dil et al (2016) extract safranin O dye using activated carbon modified with Fe 2 O 3 nanoparticles (Fe 2 O 3 -NPs-AC) as an adsorbent.…”
Section: Resultsmentioning
confidence: 82%
“…5 c show that in more than 225 μL, all the dye enters the eluent, and the equilibrium moves quantitatively toward the eluent and becomes completely desorbed. Zhang et al (2021) obtained similar results in the extraction of methylene blue (MB) dye using alumina-neutral (ALN) cartridges 44 . Dil et al (2016) extract safranin O dye using activated carbon modified with Fe 2 O 3 nanoparticles (Fe 2 O 3 -NPs-AC) as an adsorbent.…”
Section: Resultsmentioning
confidence: 82%
“…It was found that there were some discrepancies between the calculated and observed values, which may be due to the interaction of MB molecules with the substrate surface and the effect of the vibrational modes, adsorption points and adsorption directions of the adsorbed molecules on the metal surface [43,44]. At the same time, the corresponding characteristic absorption peak could still be recognized even for MB concentrations as low as 10 −7 M, which was below the maximum residue requirement of MB (0.4 ppm) [45]. This result suggests that this hydrophobic CFP@PDA@AuNPs substrate was able to rapidly and reliably detect MB.…”
Section: Application Of Hydrophobic Substrates In Residual Mb Detectionmentioning
confidence: 83%
“…The first is that MB may have been partially or completely metabolized into by-products, which are also toxic. MB is a basic phenothiazine dye that can undergo demethylation, resulting in the formation of azure A, azure B, azure C, benzidine and methylene [17,54]. For example, azure B has been shown to delay the development of the gastrula and blastula stages in the starfish Marthasterias glacialis [55].…”
Section: Discussionmentioning
confidence: 99%